Neuroprotective effects of polydatin against mitochondrial-dependent apoptosis in the rat cerebral cortex following ischemia/reperfusion injury - Gao, Youguang (Mol Med Rep, 2016)
The neuroprotective effect of polydatin (PD) against hemorrhagic shock-induced mitochondrial injury has been described previously, and mitochondrial dysfunction and apoptosis were reportedly involved in ischemic stroke. In the present study the neuroprotective effect of PD in preventing apoptosis was evaluated following induction of focal cerebral ischemia by middle cerebral artery occlusion (MCAO) in rats. PD (30 mg/kg) was administered by caudal vein injection 10 min prior to ischemia/reperfusion (I/R) injury. 24 h following I/R injury, ameliorated modified neurological severity scores (mNSS) and reduced infarct volume were observed in the PD treated group. Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining and Annexin V/propidium iodide assays demonstrated the anti-apoptotic effect of PD in the ischemic cortex. In addition, PD improved I/R injury-induced mitochondrial dysfunction, reflected by morphological observations and measurements of mitochondrial membrane potential and intracellular ATP measurement. Western blot analysis revealed an increase in B-cell lymphoma 2 apoptosis regulator (Bcl-2) expression, and a decrease in Bcl-2-associated protein X apoptosis regulator expression in the PD group in comparison with the vehicle treated group. PD treatment also prevented the release of cytochrome c from mitochondria into the cytoplasm, and blunted the activities of caspase-9 and caspase-3. Furthermore, PD treatment decreased the levels of reactive oxygen species in neurons isolated from the ischemic cortex. The findings of this study, therefore, suggest that PD has a dual effect, ameliorating both oxidative stress and mitochondria-dependent apoptosis, making it a promising new therapy for the treatment of ischemic stroke.